Does the form of the Aggregate Production Function Matter for Modelling Business Cycle Fluctuations? Lessons for Bulgaria (1999-2018) - Aleksandar Vasilev (Review of Economics and Finance, 2020)
We introduce a constant-elasticity-of-substitution (CES) production function into a real-business-cycle setup with a government sector. We calibrate the model to Bulgarian data for the period following the introduction of the currency board arrangement (1999-2018). We investigate the quantitative importance of the degree of substitutability between labor and capital in the aggregate production function, and found that aspect to matter relatively little for the ability of the model to match the magnitude of the observed business cycle fluctuations.
Keywords: E24; E32; 330; business cycles; CES aggregate production function; Bulgaria